2018
DOI: 10.1002/app.46697
|View full text |Cite
|
Sign up to set email alerts
|

A phase separation method toward PPTA–polypropylene nanocomposite separator for safe lithium ion batteries

Abstract: The building of separators with high thermal stability and security is important for lithium ion batteries. A novel, simple and successive process, which aims at coating poly-p-phenylene terephthamide (PPTA) onto commercial polypropylene (PP) separators, has been demonstrated. Without any additional binder, the PPTA nanofiber coating layer sticks to the porous PP separators by physical anchoring, endowing the composite separators with modified wettability toward electrolytes and heat resistance. Meanwhile, mig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 17 publications
0
22
0
Order By: Relevance
“…However, applying polyolefin separators is limited in high performance batteries due to the two following reasons: first, their thermal stabilities are low (commercial PE and PP grades' melting point of ∼130 and ∼165 °C, respectively) resulting in the separators deformation at high current densities of the batteries' charging lead to their warming up. Separator deformation increases probability of short circuit in its assembled battery's or even though its fire and explosion . Second, polyolefin membranes' hydrophilicities are low and consequently their liquid electrolyte uptakes and wettabilities are also low resulted in their low lithium ion transport, cell capacity, and battery life cycle …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, applying polyolefin separators is limited in high performance batteries due to the two following reasons: first, their thermal stabilities are low (commercial PE and PP grades' melting point of ∼130 and ∼165 °C, respectively) resulting in the separators deformation at high current densities of the batteries' charging lead to their warming up. Separator deformation increases probability of short circuit in its assembled battery's or even though its fire and explosion . Second, polyolefin membranes' hydrophilicities are low and consequently their liquid electrolyte uptakes and wettabilities are also low resulted in their low lithium ion transport, cell capacity, and battery life cycle …”
Section: Introductionmentioning
confidence: 99%
“…Separator deformation increases probability of short circuit in its assembled battery's or even though its fire and explosion. [13][14][15] Second, polyolefin membranes' hydrophilicities are low and consequently their liquid electrolyte uptakes and wettabilities are also low resulted in their low lithium ion transport, cell capacity, and battery life cycle. 12,16…”
mentioning
confidence: 99%
“…Moreover, the electrolyte uptake is also improved from 80% to 140%, which leads to enhancing the ionic conductivity. He et al reported the simple and successive method to modify PP separator with poly‐ p ‐phenylene terephthamide (PPTA) without using any binder. The PPTA coated PP separator improves the wettability and thermal stability of pristine PP separator.…”
Section: Types Of Separatorsmentioning
confidence: 99%
“…SEM images of PPTA nanofiber coated layer on PP separator a) surface morphology, b) internal morphology, c) cross‐section view of PPTA, d) photos of PP and PPTA coated PP separators after annealing at different temperatures for 1 h,e) images of contact angle measurements, and f) mechanical strength profiles of PP and PPTA coated PP separators. Reproduced with permission . Copyright 2018, Wiley‐VCH.…”
Section: Types Of Separatorsmentioning
confidence: 99%
“…One of the most important uses of ANFs is to prepare aramid paper. [16][17][18][19][20] Aramid paper is an essential raw material for the application of high-grade insulation and honeycombs, which strictly requires high performance of ANFs. PPTA-based ANF paper has high tensile strength, great thermal stability and excellent insulation properties.…”
mentioning
confidence: 99%